Molecular detection of flaviviruses and alphaviruses in mosquitoes (Diptera: Culicidae) from coastal ecosystems in the Colombian Caribbean (2016)
ABSTRACT:Arboviruses belonging to the genera Flavivirus and Alphavirus were detected in mosquitoes in a rural area of San Bernardo del Viento (Córdoba, Colombia). A total of 22,180 mosquitoes were collected, sorted into 2,102 pools, and tested by generic/nested reverse transcription-polymerase chain reaction. Venezuelan equine encephalitis virus, dengue virus, West Nile virus, St. Louis encephalitis virus, yellow fever virus, and Culex flavivirus were detected and identified by sequencing. The detection of arboviral pathogens in this zone represents possible circulation and indicates a human health risk, demonstrating the importance of virological surveillance activities.